PERGESERAN PEMANFAATAN SISTEM IRIGASI SEBAGAI PENYEBAB TERJADINYA BANJIR PERKOTAAN - SRIYONO FT UTP; YULIMAN ZILIWU (Jurnal Teknik Sipil dan Arsitektur, 2008)
Growth an region of agrarian fenomena which predominated by open farm for the activity of agriculture conducting, becoming to distinguish town which predominated by farm woke up, without supported by correct operation and instruction, canbe cause at downhill progressively efficiency him usage of farm and room which on pertinent region, and quality of life of area, what in the end various the condition accumulateed some regional shareses of supporter of area, and in the end of member effect of annoyed him of is continuity of growth ofvinicity region by totally. One of the consequence of friction of usage of farm, is do not be needed / progressively the minim of role of irrigation network. Changed open farm him which at first is agriculture conduct ing farm become farm woke up by the loadedness with resident activity, good for the sake of setlement, commerce / service, education, health, white colors, and various other facility, causing downhill progressively land: ground diffusion energy him coming from surface water, previous in the form of irrigation network for (he irrigating of agriculture farm, drainage network tobe for the service of town utilities (woke up). Speed of growth of open farm become farm woke up, in general do not follow, and can make balance to by ready of infrastructure network, specially adequate drainage network, so that many farmses woke up which not yet served with drainage network. In a condition friction of usage of such farm quickly take place (from open farm become farm woke up), that happened is exploiting of irrigation network which have preexisted, becoming drainage network, without passing process engineer network system which was planned eminently. So that ascertained of big contribution member for possibility the happening of floods and pond in urban region, and area of him. This research is basically expected can guide member at various-phenomenon friction of usage of farm, with friction of exploiting of irrigation network system become drainage network, what isn't it become one of cause the happening of floods and pond at one particular region (town), which is him cikal will is open farm (agriculture conducting) becoming farm woke up, as commended in town planology plan. History growth of town isn't it, that some towns which early from agrarian fenomena become to distinguish strong town, without planning better friction of exploiting of irrigation network become drainage network as consequence growth of town, tend to to be given on to annual floods. Town of Klaten raised as case in this research, is expected can represent pre of[is condition of region upon which research study. Â